Ag/Au Mixed Sites Promote Oxidative Coupling of Methanol on the Alloy Surface. Issue 16 (13th March 2014) - Xu, Bingjun; Siler, Cassandra G. F.; Madix, Robert J.; Friend, Cynthia M.
Abstract Nanoporous gold, a dilute alloy of Ag in Au, activates molecular oxygen and promotes the oxygen‐assisted catalytic coupling of methanol. Because this trace amount of Ag inherent to nanoporous gold has been proposed as the source of oxygen activation, a thin film Ag/Au alloy surface was studied as a model system for probing the origin of this reactivity. Thin alloy layers of AgxAu1−x, with 0.15≤x≤0.40, were examined for dioxygen activation and methanol self‐coupling. These alloy surfaces recombine atomic oxygen at different temperatures depending on the alloy composition. Total conversion of methanol to selective oxidation products, that is, formaldehyde and methyl formate, was achieved at low initial oxygen coverage and at low temperature. Reaction channels for methyl formate formation occurred on both Au and Au/Ag mixed sites with a ratio, as was predicted from the local 2‐dimensional composition.